Analytical Study on the Breakdown Characteristics of Si-Substrated AlGaN/GaN HEMTs With Field Plates - Jianhua Liu; Yu-Feng Guo; Jun Zhang; Jiafei Yao; Maolin Zhang; Chenyang Huang; Ling Du (IEEE Journal of the Electron Devices Society, 2020)
The breakdown voltage model of Si-substrated AlGaN/GaN HEMTs with gate and drain field plates is proposed in this work. The silicon substrate and GaN buffer are considered as the depletion region in the modeling process. The analytical model shows great simplicity and veracity. It gives physical insights into the breakdown characteristics of the AlGaN/GaN HEMTs. The avalanche breakdown occurs at the field plate's edge in lateral structure or at the interface in vertical structure. According to the analytical model, the relationship between the lateral breakdown and the vertical breakdown is demonstrated in this work. The breakdown location is affected by the variation of the structure parameters, including gate-to-drain distance, buffer thickness and field plates' lengths. With the aid of the analytical model, effective guidance for device optimization to achieve high performance can be obtained.